PENGEMBANGAN MUTU PADA PEMASARAN JASA - Rahayu, Amy Y.S. (FIA UB, 2007)
Service areÂ different from goods in both their nature and delivery system. They rely more heavily than goods on customer, client perceptions, and expections. Characteristics of services revolve around four main qualities, their intangibility, inseparability and perish ability. So, quality improvement is very important because both the service provider and the service customer are actively in the delivery process and input and output of the service encounter. The importance of clear customer focus in this relationship (transaction) is reflected in both marketing and operational management. Service managers need to clearly identify the nature of their services and their specific customer markets along their contact